P242 Cerebellar tDCS effects on the adaptation of arm reaching movements to force-field and visuomotor perturbations. Issue 3 (March 2017) - Mamlins, A.; Hulst, T.; Donchin, O.; Timmann, D.; Claaßen, J.
Abstract : Introduction: Studies with transcranial direct current stimulation (tDCS) have shown that anodal tDCS of the cerebellar hemispheres leads to faster adaptation of arm reaching movements to visuomotor rotation and force field perturbations in healthy subjects (Galea et al., 2011; Herzfeld, 2014 ). Objectives: The first aim of the present study was to replicate the findings mentioned above. The second aim was to investigate whether tDCS effects differ depending on the onset of stimulation, that is during or after an initial baseline phase. Patients and Methods: A total of 120 healthy and right-handed subjects (60 females, aged 18–31 years, mean 23.2 ± 2.7) were tested. Subjects moved a cursor with a two-joined manipulandum to one of eight targets presented on a screen. There were three baseline blocks, one adaptation block and three washout blocks. 60 subjects performed a force field (FF) task, 60 subjects a visuomotor adaptation task (VM). During the adaptation block, a velocity-dependent clockwise perpendicular force (23 N ·m −1 ·s −1 was applied in FF and a 30° clockwise rotation in VM. Equal numbers of subjects received anodal, cathodal or sham stimulation over the right cerebellum beginning either in the third baseline or in the adaptation block. The maximum error (ME), final error (FE) and perpendicular velocity 55 ms after movement onset (PV) were assessed. Results: During FF and VM adaptation subjects significantly improved regarding ME, FE and PV ( p  < 0.001, analysis of variance with repeated measures). There were no significant effects of stimulation, no significant effects of onset of stimulation and no significant interactions (all p -values > 0.05). The same was true for the washout blocks. Conclusion: Our results show that prior possible clinical application, future experiments are needed to determine which cerebellar tDCS and task parameters lead to robust tDCS effects. Funded by ELAN and DFG TI 239/16-1.